2017
DOI: 10.1007/s11695-017-2802-7
|View full text |Cite
|
Sign up to set email alerts
|

Massive Weight Loss Obtained by Bariatric Surgery Affects Semen Quality in Morbid Male Obesity: a Preliminary Prospective Double-Armed Study

Abstract: The massive weight loss obtained with bariatric surgery was associated with an improvement in some semen parameters. The correlations found between weight loss and semen parameter variations after surgery suggest that these might occur early downstream of the testis and more slowly than the changes in the sex hormones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 36 publications
4
58
0
1
Order By: Relevance
“…El Bardisi et al was able to demonstrate improvement in sperm concentration in those that were oligospermic or azoospermic prior to sleeve gastrectomy (P<0.05) along with significant increases in serum testosterone (P<0.001) ( 92 ). In a prospective double-armed study comparing semen parameters in men undergoing gastric bypass versus non-operative management, Samavat et al demonstrated improvements in progressive/total sperm motility and number; however only semen volume and viability were found to have sustained significant improvements (P<0.05) after surgery ( 93 ).…”
Section: Future Considerationsmentioning
confidence: 99%
“…El Bardisi et al was able to demonstrate improvement in sperm concentration in those that were oligospermic or azoospermic prior to sleeve gastrectomy (P<0.05) along with significant increases in serum testosterone (P<0.001) ( 92 ). In a prospective double-armed study comparing semen parameters in men undergoing gastric bypass versus non-operative management, Samavat et al demonstrated improvements in progressive/total sperm motility and number; however only semen volume and viability were found to have sustained significant improvements (P<0.05) after surgery ( 93 ).…”
Section: Future Considerationsmentioning
confidence: 99%
“…Three studies were included in our study [8][9][10]. The searching process is summarized in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…They found the changes of BMI was associated with in sperm volume (r=0.618, p<0.05) with statically significant. MacDonald et al performed a cross-sectional study recruit 514 men suggested that the sperm volume (r=0.02, p>0.05) [8].…”
Section: Discussionmentioning
confidence: 99%
“…11 Paternal obesity is also acknowledged to negatively affect assisted reproduction outcomes. 12 However, results are conflicting regarding the effect of significant weight loss on semen analysis parameters because 'improved', [13][14][15][16][17] 'no change' 18 and 'deterioration' 19,20 have all been reported.…”
Section: Obesity and Weight Lossmentioning
confidence: 99%